TRIM65 Suppresses oxLDL-induced Endothelial Inflammation by Interaction with VCAM-1 in Atherogenesis - Ma, Xiao-Feng; Zhou, Yi-Ren; Zhou, Zhi-Xiang; Liu, Hui-Ting; Zhou, Bo-Bin; Deng, Nian-Hua; Zhou, Kun; Tian, Zhen; Wu, Ze-Fan; Liu, Xi-Yan; Fu, Ming-Gui; Jiang, Zhi-Sheng (Current Medicinal Chemistry, 2024)
Background and Objective: Endothelial cell activation, characterized by increased levels of vascular cell adhesion molecule 1 (VCAM-1), plays a crucial role in the development of atherosclerosis (AS). Therefore, inhibition of VCAM-1-mediated inflammatory response is of great significance in the prevention and treatment of AS. The tripartite motif (TRIM) protein-TRIM65 is involved in the regulation of cancer development, antivirals and inflammation. We aimed to study the functions of TRIM65 in regulating endothelial inflammation by interacting with VCAM-1 in atherogenesis. Methods and Results: In vitro, we report that human umbilical vein endothelial cells (HUVECs) treated with oxidized low-density lipoprotein (oxLDL) significantly upregulate the expression of TRIM65 in a time- and dose-dependent manner. Overexpression of TRIM65 reduces oxLDL-triggered VCAM-1 protein expression, decreases monocyte adhesion to HUVECs and inhibits the production of the inflammatory cytokines IL-1β, IL-6, IL-8, and TNF-α as well as endothelial oxLDL transcytosis. In contrast, siRNA-mediated knockdown of TRIM65 promotes the expression of VCAM-1, resulting in increased adhesion of monocytes and the release of the inflammatory cytokines IL-1β, IL-6, IL-8, and TNF-α and enhances endothelial oxLDL transcytosis. In vivo, we measured the high expression of TRIM65 in ApoE-/- mouse aortic plaques compared to C57BL/6J mouse aortic plaques. Then, we examined whether the blood levels of VCAM-1 were higher in TRIM65 knockout ApoE-/- mice than in control mice induced by a Western diet. Furthermore, Western blot results showed that the protein expression of VCAM-1 was markedly enhanced in TRIM65 knockout ApoE-/- mouse aortic tissues compared to that of the controls. Immunofluorescence staining revealed that the expression of VCAM-1 was significantly increased in atherosclerotic plaques of TRIM65-/-/ApoE-/- aortic vessels compared to ApoE-/- controls. Mechanistically, TRIM65 specifically interacts with VCAM-1 and targets it for K48-linked ubiquitination. Conclusion: Our studies indicate that TRIM65 attenuates the endothelial inflammatory response by targeting VCAM-1 for ubiquitination and provides a potential therapeutic target for the inhibition of endothelial inflammation in AS.
Keywords: endothelial inflammation